W‐band power amplifier using broadband impedance‐transforming coupled line couplers. Issue 4 (April 2015) - Kim, Jungsik; Lee, Sangho; Lee, Seokchul; Kim, Wansik; Kwon, Hosang; Kwon, Youngwoo; Jeong, Jinho
ABSTRACT In this letter, a compact and broadband impedance‐transforming 90° hybrid is proposed, where two coupled lines with different characteristic impedances are cascaded to transform 50 to 25 Ω. The designed 50–25 Ω transforming coupler on a GaAs substrate shows a measured insertion loss of 1.1 dB with a return loss of 29.0 dB at 77 GHz. The insertion loss is lower than 2.0 dB in the range from 30 to 97 GHz. The proposed impedance‐transforming couplers are used in the design of a W‐band balanced power amplifier (PA) with a port impedance of 25 Ω, which allows the compact and broadband design of matching circuits in the PA. The PA fabricated by a 0.15‐μm GaAs pHEMT process shows a small‐signal gain of 13.3 dB at 79.5 GHz with a 3‐dB bandwidth of 21.4% (from 72 to 89 GHz). The measured output power is as high as 16.7 dBm at 75 GHz. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:803–806, 2015